Analysis and Countermeasures of Regional Economic Differences in Sichuan Province Driven by Digital Economy - Zuo, Hang; Miao, Guodong; Pang, Xinyu (Journal of Global Economy, Business and Finance, 2025)
Objective: This paper takes the urban agglomerations in Sichuan Province region as the research object, aiming to explore the status of spatial economic linkages in the urban agglomerations in Sichuan Province region and promote its regional coordinated development. Methods: The inductive summary method, theoretical analysis method, qualitative analysis method and quantitative calculation method are used. Through extensive literature review and data collection, relevant theories are sorted out, and the improved gravity model is adopted for measurement. Conclusions: 1) There are shortcomings in the spatial economic linkages of the urban agglomerations in Sichuan Province region, including backward urban economic development levels, unbalanced urban scale structure systems, insufficient urban industrial division and cooperation, lagging construction of transportation connection channels, and insufficient administrative system coordination and support. 2) Targeted suggestions are put forward, including optimizing the urban industrial layout, and promoting regional industrial division, inter - regional coordination and industrial cooperation in the marginal areas of Sichuan Province. 3) Strengthening the construction of transportation facilities, building a comprehensive 1-hour transportation circle and improving transportation hubs. 4)Improving the overall coordination mechanism, establishing an integrated market and exploring the urban cooperation benefit balance mechanism to strengthen the economic linkages of the urban agglomeration.